Gambaran Penggunaan Obat Antihipertensi Pada Pasien Lansia Dengan Diabetes Melitus di RSUD Aloei Saboe Tahun 2024 - Lairi, Nurain; Tuloli, Teti Sutriyati; Rasdianah, Nur (-, 2026)
Hypertension is recognized as a clinical condition that may lead to various disease-related complications, including diabetes mellitus. Both conditions are commonly observed in the elderly population. Advancing age is associated with physiological changes, such as decreased vascular elasticity and reduced peripheral tissue sensitivity to insulin. This study aimed to describe the pattern of antihypertensive drug utilization among elderly patients with diabetes mellitus at Prof. Dr. Hi. Aloei Saboe Regional General Hospital, Gorontalo City, in 2024. This study employed an observational design with a descriptive retrospective approach. Data were collected from the medical records of 30 patients with hypertension and comorbid diabetes mellitus who met the inclusion criteria. The results indicated that the majority of patients were female (90%), with the highest proportion observed in the 60–63 years age group (56.6%). Based on the analysis of antihypertensive drug classes, calcium channel blockers (CCBs) were the most frequently prescribed, with amlodipine accounting for 56% of prescriptions. Furthermore, in combination therapy involving antihypertensive and antidiabetic agents, the most commonly prescribed regimen was amlodipine combined with Sansulin Log-G (38%).